Pelaksanaan Remedial Pada Siswa Sosiologi di SMAN 1 Kecamatan Akabiluru Kabupaten Lima Puluh kota - Pratiwi, Widya Okta; Junaidi, Junaidi (Naradidik: Journal of Education and Pedagogy, 2022)
This research is motivated by the existence of remedial learning that given by the teacher for class XI IPS at SMAN 1 Akabiluru District District of Fifty Cities. This is evidenced by students who still have not to achieve KKM in sociology, there are 34 students out of 65 students. This study aims to determine the implementation of remedial on students sociology at SMAN 1 Akabiluru Kabupaten Lima Puluh Kota. Technique selection of informants by using purposive sampling with a number of 16 informants consisting of 14 sociology students who took remedial and 2 teachers of sociology. Data collection techniques are by observation, in-depth interviews and documentation. Data analysis carried out with the interactive model of Miles and Huberman which consists of reducing data, presentation of data and drawing conclusions. Theory used in this study Agil by Talcon Parson, the results of this study indicate that remedial sociology at SMAN 1 Akabiluru sub-district is carried out in three forms, namely tutoring, giving assignments and reteaching, the timing of this remedial implementation is routinely done after students take the exam and how to present the material is given by provide a stimulus in the form of essay questions that are easy to understand and can be analyzed students through real life so that students can better understand the material learning. The assessment given by the teacher is in the form of numbers according to the KKM which has been determined is 75.